Antibiotics sensitivity status and antibiogram patterns of aerobic bacterial isolates from surgical site infections - Arora, Balvinder Singh; Rajan, Santhosh; Mohil, Ravinder; Mathur, Neeraj Narayan (International Journal of Research in Medical Sciences, 2019)
Background: Surgical Site Infections (SSIs) are the third most common nosocomial infections. Emergence and spread of drug resistant strains have been found to pose a serious challenge in the management of such infections. There is limited information on the epidemiology of such pathogens. The antibiotic sensitivity patterns of aerobic bacterial isolates from post-operative SSIs show wide variations that lead to difficulties in empirical selection of the right kind of drug for treatment. Properly planned studies about antibiotic sensitivities patterns of such isolates can help in judicious management of SSIs and cause reduction in morbidity and mortality. Methods: A total of 50 patients diagnosed by the surgeon and fulfilling the case definition of SSI, were studied for bacteriological analysis. All the clinical specimens were cultured and identified applying standard culture techniques. The aerobic bacterial isolates were subjected to antimicrobial susceptibility testing by Kirby Bauer Disc Diffusion method to arrive at the drug sensitivity patterns. Data were entered in MS Excel spread sheet and analysed using SSPP software version 21.00 Results: A total of 32 patterns of sensitivity were observed. For Esch. coli, a total of nine patterns were observed. All strains of Esch. coli were found sensitive to tigecycline (100%) and colistin (100%). For Klebsiella spp. a total of 9 patterns were obtained with TIG-COL being the predominant pattern in 6 cases. For Acinetobacter spp. only colistin was found most effective drug. In case of Pseudomonas aeruginosa, except colistin (100% sensitivity), there were wide variations in sensitivity with imipenem (71%) as next most effective drug. In Proteus spp. - most of the in-use drugs were effective except cephalosporins. Among gram positive organisms, only three strains of Staphylococcus aureus were isolated, and these were MRSA (100%). Two strains of enterococcus were isolated, and these showed sensitivity to linezolid only. Conclusions: Wide variations in sensitivity status observed in the study are suggestive that antibiotic usage should be tailored to individual needs and proper selection of antibiotics for management of SSIs must be guided by laboratory antibiogram.